2004
DOI: 10.1001/archotol.130.2.201
|View full text |Cite
|
Sign up to set email alerts
|

Age-, Site-, and Time-Specific Differences in Pediatric Deep Neck Abscesses

Abstract: To clarify presentations, organisms, and locations of deep neck abscesses in children.Design: Retrospective review.Setting: Tertiary children's hospital. The study population comprised 169 patients younger than 19 years who were surgically treated for deep neck abscesses between 1989 and 1999.Main Outcome Measure: Resolution of abscess.Results: Neck mass (91%), fever (86%), cervical adenopathy (83%), poor oral intake (66%), and neck stiffness (59%) were common in all ages. Patients younger than 4 years, compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
102
5
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(135 citation statements)
references
References 23 publications
23
102
5
5
Order By: Relevance
“…Multiple space involvement was seen in 11% of our patients. Submental space involvement was most common in our study seen in 25% of cases followed by paraphyrangeal (18%), submandibular (16%) which is in contrast to a study reported by Coticchia et al [10], where the most commonly encountered sites of abscesses in the head and neck region of paediatric patients were retropharyngeal or parapharyngeal spaces followed by anterior or posterior triangle and submandibular or submental regions, respectively. Parotid space abscesses was seen in our study in 12% of patients while one study [10] reported it only in 1% of patients.…”
Section: Clostridium Gp 1 Acinetobactercontrasting
confidence: 98%
See 2 more Smart Citations
“…Multiple space involvement was seen in 11% of our patients. Submental space involvement was most common in our study seen in 25% of cases followed by paraphyrangeal (18%), submandibular (16%) which is in contrast to a study reported by Coticchia et al [10], where the most commonly encountered sites of abscesses in the head and neck region of paediatric patients were retropharyngeal or parapharyngeal spaces followed by anterior or posterior triangle and submandibular or submental regions, respectively. Parotid space abscesses was seen in our study in 12% of patients while one study [10] reported it only in 1% of patients.…”
Section: Clostridium Gp 1 Acinetobactercontrasting
confidence: 98%
“…Submental space involvement was most common in our study seen in 25% of cases followed by paraphyrangeal (18%), submandibular (16%) which is in contrast to a study reported by Coticchia et al [10], where the most commonly encountered sites of abscesses in the head and neck region of paediatric patients were retropharyngeal or parapharyngeal spaces followed by anterior or posterior triangle and submandibular or submental regions, respectively. Parotid space abscesses was seen in our study in 12% of patients while one study [10] reported it only in 1% of patients. Ryan C. Cmejrek et al [17] in a study on 25 paediatric patients found that the more superficial anterior and posterior triangle abscesses (11/25) tend to be more common than those in the parapharyngeal (5/25) or retropharyngeal (3/25) spaces.…”
Section: Clostridium Gp 1 Acinetobactercontrasting
confidence: 98%
See 1 more Smart Citation
“…O abscesso retrofaríngeo pode ser diagnosticado apenas pela tomografia computadorizada (1). Na população pediátrica, as infecções de vias aéreas superiores e as tonsilites são as causas mais comuns de abscesso cervical, sendo os espaços retrofaríngeo e parafaríngeo os mais acometidos, principalmente em crianças acima de 1 ano (15).…”
Section: Discussionunclassified
“…Os agentes etiológicos mais comuns dos abscessos cervicais são os estreptococos e os estafilococos, assim como na TA, porém a média de idade do acometimento é um pouco inferior (4,1 anos) à da TA (6 anos), e 75% dos casos ocorrem antes do 5 anos de idade (6,7,15,16). Isso provavelmente é por causa da atrofia dos nódulos linfáticos após o terceiro e quarto ano de idade, uma vez que a formação do abscesso cervical dá-se pela propagação de infecções da nasofaringe, dos seios paranasais e do ouvido médio para o espaço profundo do pescoço, diretamente por continuidade, ou por drenagem linfática para os nódulos linfáticos deste espaço (16).…”
Section: Discussionunclassified